Assessment of Low-Level Laser Therapy Effects After Extraction of Impacted Lower Third Molar Surgery - Raiesian, Shahrokh; Khani, Mehdi; Khiabani, Kazem; Hemmati, Ershad; Pouretezad, Mohammad (Journal of Lasers in Medical Sciences, 2017)
Introduction: The aim of this study was to assess the effect of low-level laser therapy (LLLT) on pain, swelling and maximum mouth opening in patients undergoing third molar surgery. Methods: A prospective, randomized double-blind study was undertaken on 44 patients at the Dental School, Ahvaz Jundishapur University of Medical Sciences, in 2015. A low-level laser was randomly applied on one of the two sides after surgery of 15 patients. The experimental side received 18 J/cm2 of energy density, wavelength of 980 nm, and output power of 1.8 W. On the control side, a hand-piece was applied intra-orally, but laser was not activated. In addition, in order to evaluate trismus, 13 patients were treated by unilateral laser therapy and 16 patients did not receive laser therapy at all. The laser was administered intraorally on two points of vestibular and lingual sides at 1 cm from the surgery site, and extraorally at the emergence of the masseter muscle, immediately after surgery, and repeated 24 hours later. The pain, swelling and maximum mouth opening (MMO) were compared between the two groups at 24 hours and a week after surgery. Results: The mean score of pain 24 hours after surgery in the laser therapy group (2.3 ± 3.5) was significantly lower than the mean score of pain in the drug therapy (4.19 ± 3.09) (P = 0.036). Moreover, the mean score of pain at one week after surgery in the laser therapy group (0.13 ± 2.33) was significantly lower than the drug therapy group (1.43 ± 2.45) (P = 0.046). The amount of swelling according to different measurements did not significantly differ between the two groups neither at 24 hours nor at 1 week after surgery. Conclusion: Our findings showed that LLLT was useful in reducing pain and could slightly reduce swelling compared to drug therapy in impacted third molar surgery.